Breeding biology of the Northern Pintail Anas acuta at the edge of its southwestern Palearctic range - Ibáñez, Fernando; Calderón, Juan; Amat, Juan A. (Wildfowl, 2023)
One of the most southern breeding sites of the Northern Pintail Anas acuta in the SW Palearctic is in the Guadalquivir marshes (southwest Spain), part of which includes Doñana National Park. Breeding was recorded in 45.7% out of 46 years and was more frequent in those seasons in which the preceding autumn/winter was rainy, suggesting that the species behaved as an opportunistic breeder. Egg-laying started in late March–early April, earlier than in more northern sites. Clutch size and nesting success were similar to those of other populations in Europe and North America. There was a tendency for brood desertion of older ducklings by females. As breeding statistics are similar to those at other sites, the breeding population in the Guadalquivir marshes should not be considered as a peripheral population from an ecological point of view. The size of the breeding population in the Guadalquivir marshes decreased throughout the 20th century. Because the Pintail depends on high water levels to breed in the Guadalquivir marshes, and overexploitation of water resources is increasing in the Doñana area, breeding of this species at this site may be compromised over the next decades.